The Impact of the Implementation of the Merit System on Independence, Justice and Transparency as KPK Law Enforcement Officers: Before and After Changes to the KPK Law Regarding Rewards and Punishments - Bahiyyah, Saidul; Makaliwe, Willem A. (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to determine whether there is a relationship between the implementation of the merit system and the professionalism, commitment, competence, and objectivity of KPK investigators, and to determine the differences in professionalism, commitment, competence, and objectivity of KPK investigators before and after the implementation of the merit system. To this end, this study used a mixed research approach, distributing questionnaires and conducting interviews with several KPK employees. The planned number of respondents was 92 people, but only 60 people returned questionnaires that were eligible for analysis (response rate 65%). Hypothesis testing was conducted using non-parametric statistics Spearman Rank correlation and Wilcoxon difference test. Regression and also Qualitative Sequential Analysis were conducted to confirm the results. The results prove that the implementation of the merit system has a significant positive impact on aspects of professionalism, commitment, competence, and objectivity. This study also contributes to the consideration of policy formulation in an effort to improve the professionalism, commitment, competence, and objectivity of KPK law enforcement officers.